Morality and Expression of Religious Moderation in "Pecinan” Town - Sumedi Sumedi; Husna Nashihin; M. Daud Yahya; Rochanah Rochanah; Noor Aziz (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The moral value and expression of religious moderation in “Pecinan” (Chinatown) in this study are values reflected in the interaction between Pondok Pesantren Kauman and the Chinese ethnic community in Lasem, Rembang. This field study has four (4) research focuses, namely: 1) the interaction of religious moderation in Chinatown, 2) the urgency of religious moderation practices in Chinatown, 3) the practice of religious moderation in Chinatown, and 4) the values of religious moderation in Chinatown. The urgency of religious moderation in Chinatown can be mapped into two (2), which are the theological and sociological urgencies. The practice of religious moderation in Chinatown is reflected physically in the acculturation of Javanese-Arab-Chinese buildings, as well as non-physically in the teaching of Islamic values rahmatan lil ‘alamin. The values of religious moderation in Chinatown include infitah (inclusive), tawassuth (moderate), musawah (equality), and tawazun (balanced).